HUBUNGAN PANJANG SARAF ULNARIS DI KOMPARTEMEN POSTERIOR DENGAN PANJANG LENGAN ATAS SEBAGAI ACUAN TERAPI - Regina Marvina Hutasoit,* Vita Murniati Tarawan Lubis,* Arifin Soenggono* (NEURONA, 2018)
INTRODUCTION ULNAR NERVE IS THE SECOND MOST COMMON AFFECTED NERVE BY COMPRESSION IN UPPER EXTREMITY MEDIAL INTERMUSCULAR SEPTUM SEPARATING UPPER ARM INTO ANTERIOR AND POSTERIOR COMPARTMENTS IS SUSPECT TO BE THE SITES OF ULNAR NERVE COMPRESSION VARIOUS EXAMINATIONS ATTEMPT TO LOCATE ACCURATE NERVE COMPRESSION SITES TO MINIMIZE SURGERY SIDE EFFECTS